Series and Parallel Arc Fault Detection in Electrical Buildings Based on Discrete Wavelet Theory - Saeed, Elaf Abed; Abdulhassan, Khalid M.; Al-Atbee, Osama Y. K. (Iraqi Journal for Electrical and Electronic Engineering, 2021)
Electrical issues such as old wires and faulty connections are the most common causes of arc faults. Arc faults cause electrical fires by generating high temperatures and discharging molten metal. Every year, such fires cause a considerable deal of destruction and loss. This paper proposes a new method for detecting residential series and parallel arc faults. A simulation model for the arc is employed to simulate the arc faults in series and parallel circuits. The fault features are then retrieved using a signal processing approach called Discrete Wavelet Transform (DWT) designed in MATLAB/Simulink based on the fault detection algorithm. Then db2 and one level were found appropriate mother and level of wavelet transform for extracting arc-fault features. MATLAB Simulink was used to build and simulate the arc-fault model.